O processo de socialização profissional: estudo com secretários executivos em organizações cearenses - Pontes, Emiliano Sousa (2017)
The phenomenon of professionalization, considered a propeller of the development of modern society, is approached in Sociology of Professions under two traditional theoretical conceptions: functionalism and symbolic interactionism (MENEGHETTI, 2009). In this context, which emphasizes interactions and social processes in the study of professions, there is the theme of professional socialization, which consists of a process of insertion of the individual into a profession, encompassing the learning and practical application of knowledge, skills, norms and values required for professional practice (BORGES, ALBUQUERQUE, 2014). In this perspective, the present research aims to analyze the process of professional socialization of executive secretaries in organizations of Ceará, according to the theoretical model synthesized by Kramer et al. (2013), who considers that professional socialization comprises three phases: separation from academy, transition to professional practice and integration into professional roles and communities. In this way, specifically, it is sought to investigate how the knowledge, skills, norms and values inherent in the profession of executive secretary in academic formation occurs, verify how the knowledge, skills, norms and values inherent in the profession of executive secretary are applied in professional practice and analyze the main and secondary professional roles played by executive secretaries and their engagement in professional communities. This research is qualitative, descriptive, carried out through semistructured interviews with fifteen executive secretaries who work in organizations located in the state of Ceará. The data are treated through the content analysis and operationalized in the software ATLAS.ti 7. As the main results achieved, it can be mentioned that: in the academic formation, the learning through the regulation law and the Code of Ethics of the profession was the most evident; in professional practice, situations of contradiction occur due to the lack of knowledge and devaluation of the profession; in integration into professional roles and communities, counseling is the most important role and engagement in professional communities does not occur. In general, the results contribute to filling the gap in the empirical literature that addresses socialization in the professions linked to organizational management, as well as promoting the scientific advance of the Executive Secretariat.